2015
DOI: 10.1167/iovs.15-18038
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence Tomography of Mouse Ocular Surface Epithelial Stem Cells and Their Niche Microenvironment

Abstract: PURPOSE. Currently, there are no definitive immunomarkers for epithelial stem cells (corneal and conjunctival) or their poorly understood niche microenvironment. The H2B-GFP/K5tTA mouse enables visualization of label-retaining cells (LRCs), which exhibit the functional marker of stem cell quiescence. We used immunofluorescence tomography to evaluate putative stem cell markers and LRCs of the mouse ocular surface.METHODS. H2B-GFP/K5tTA mice were pulsed for 56 days and then chased with doxycycline to label LRCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
(37 reference statements)
1
27
1
1
Order By: Relevance
“…The amount of ABCG2 + cells in in vitro LESC cultures has been indeed controversial; there is a big variance between the used methods 25 26 27 ; 2–4% of the LESCs cultured on mice feeder cells were found positive 28 , while the same amount could be reached with keratocyte medium cultivation as well 25 (similar to our cultured CSMSCs), and in other model, the cell suspension and explant showed 50–85% positivity 27 . Interestingly, another ATP-binding cassette transporter (ABCB5) has been suggested to be an in situ specific LESC marker 29 30 , however, in our dataset, neither the in vitro cultured LESCs nor the CSMSCs expressed ABCB5. Interestingly, a weak expression could be detected only in one of the BMMSC donors (see Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 68%
“…The amount of ABCG2 + cells in in vitro LESC cultures has been indeed controversial; there is a big variance between the used methods 25 26 27 ; 2–4% of the LESCs cultured on mice feeder cells were found positive 28 , while the same amount could be reached with keratocyte medium cultivation as well 25 (similar to our cultured CSMSCs), and in other model, the cell suspension and explant showed 50–85% positivity 27 . Interestingly, another ATP-binding cassette transporter (ABCB5) has been suggested to be an in situ specific LESC marker 29 30 , however, in our dataset, neither the in vitro cultured LESCs nor the CSMSCs expressed ABCB5. Interestingly, a weak expression could be detected only in one of the BMMSC donors (see Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 68%
“…Sox9 has also been previously identified in limbal epithelial cells by microarray analysis of scraped epithelial samples 44 and transcriptome analysis of microdissected limbal epithelial crypts 37 as well as in cultivated human limbal epithelial keratinocytes 45 , but was not further analysed in situ . In addition, Sox9 has been identified as a marker of slow-cycling corneal epithelial stem cells in mouse eyes 46 , 47 . In extending this anecdotal evidence for a role of Sox9 in the human limbal stem cell niche, the present study demonstrated a striking differential sub-cellular localization of Sox9 in basal LEPC clusters and their progeny: Whereas LEPCs showed mainly cytoplasmic staining for Sox9, indicative of protein synthesis, suprabasal limbal and corneal epithelial cells showed exclusively nuclear localization suggestive of TF activity.…”
Section: Discussionmentioning
confidence: 99%
“…Prdm1 is the key regulator of primordial germ cells (PGCs) in the embryo39 but it is also linked to stem cell pluripotency and maturation in non-germline cells404142434445464748. Here it was not a specific marker of the germline as it could be detected in dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Only Prdm1 and Iftm3 , often regarded as germline markers 38 , were present in freshly isolated ovarian cells following FACS with DDX4 C25 antibody. Prdm1 is the key regulator of primordial germ cells (PGCs) in the embryo 39 but it is also linked to stem cell pluripotency and maturation in non-germline cells 40 41 42 43 44 45 46 47 48 . Here it was not a specific marker of the germline as it could be detected in dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%